In vitro and In vivo Interaction of Ketorolac Tromethamine and Cefixime Trihydrate - Flora, Mokaddas; Tahsin, Rafat; Chowdhury, Jakir Ahmed; Kabir, Shaila; Amran, Md Shah; Chowdhury, Abu Asad (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Drug-drug interaction, a major impediment towards safe and effective pharmacotherapy, often leads to adverse outcome or therapeutic failure if not properly identified. The present study employed a number of in vitro and in vivo methods to conduct a thorough investigation of the interaction potential between ketorolac tromethamine (nonsteroidal anti-inflammatory drug) and cefixime trihydrate (beta-lactam antibiotic). UV-Visible spectrophotometry, FTIR and DSC were carried out to analyze the interaction of ketorolac and cefixime in vitro. UV-visible spectrophotometric study at different pH showed hyperchromic shift and blue shift (hypsochromic shift) in the mixture of the studied drugs compared to ketorolac alone. In contrast, only hyperchromic shift was found in the mixture when compared to cefixime alone. In DSC study, the melting endotherm of ketorolac tromethamine shifted from 169.62°C to 149.99°C in the 1:1 mixture. Again, the FTIR spectrum showed that in 1:1 mixture, the lactam (C=O) band of cefixime trihydrate shifted from 1771.68 cm-1 to 1718.63 cm-1, the amide carbonyl band (-CONH) moved from 1669.45 cm-1 to 1616.4 cm-1 and the -OH band moved from 3296.46 cm-1 to 3397.72 cm-1 which might be indicative of interaction between these two drugs. The in vivo study in rat model was designed to determine whether cefixime has any significant impact on the analgesic activity of ketorolac. In vitro antimicrobial effect was also performed to evaluate the effect of ketorolac on cefixime. The findings from these study suggested that neither ketorolac nor cefixime imparted any deleterious impact on the biological property of each other which might indicate that co-administration of ketorolac and cefixime are therapeutically effective and safe. Dhaka Univ. J. Pharm. Sci. 22(2): 137-146, 2023 (December)